Karakteristik Profesionalisme dalam Konsep Kepala Negara Nabi Muhammad - St Magfirah Nasir (IAIN Bengkulu, 2021)
The focus of this research is analyze the characteristics of the head of state of the Prophet Muahmmad saw based on the traditions of professional leadership. This research has a problem, such as: How is the characteristics of the leadership of the Prophet Muhammad as head of state? How is the analysis of the traditions of the leadership of the Prophet Muhammad as head of state ?. The purpose of this research is the role of the Prophet Muhammad in Medina when he was the head of state, to determine the form of analysis of the traditions of the leadership of the Prophet Muhammad as head of state in the quality of hadith. The research approach of this thesis uses hadith, philosophical and political criticism. The type of research used is qualitative, including primary data sources, namely data obtained directly from source books and secondary data, namely obtained from systematized writing. The findings of this research shows that the leadership traditions about professionalism have accommodated the role of the Prophet Muhammad as head of state, because it is covered in the characteristics of prophetic leadership, such as: the ability to carry out the mandate, balance justice for society, realize one's strengths and weaknesses, behave honestly and the ability to war.